Performance of graphene oxide doped polyaniline composite electrodes for energy storage: Effects of in-situ synthesis - Mupit, Muazzin; Islam, Muhammad Remanul; Azam, Mohd Asyadi; Smdani, Md Gulam; Mohd Yunus, Rosli; Firouzi, Amin; Ong, Siew Kooi (Springer, 2022)
Two different synthesis processes, in-situ polymerization and ex-situ polymerization process, were implied to identify the impact of these processes on the properties of the graphene oxide (GO) doped conductive polyaniline (PANi)-based electrode materials. This study focused on the improvement of various properties of PANi/GO composite materials produced through the in-situ polymerization process.